Influence of abiotic factors on seasonal dynamics of pink stem borer Sesamia inferens Walker in rice-wheat cropping system of India - singh, beant; Kular, J S (Journal of Cereal Research, 2015)
Pink stem borer Sesamia inferens (Lepidoptera: Noctuidae) (PSB) is originally a pest of rice but in recent past, it has also emerged as pest on wheat crop. The pinkish caterpillar of S. inferens bores into stem and kills central shoots forming â€˜dead heartsâ€™. Meteorological factors play an important role in incidence, population build-up and damage of insect pests. Most of the studies in context to PSB seasonal abundance have been carried out on individual crops e.g. on rice, wheat or maize and only few reports are available on population dynamics of PSB throughout the year in rice-wheat cropping system. To meet this objective, seasonal abundance of PSB incidence was investigated on different host throughout the year during 2010-11 and 2011-12. The correlation between incidence of PSB and different abiotic factors viz. temperature, relative humidity and rainfall were also worked out. The results indicated that maximum incidence of PSB was observed in the months of September-October when maximum, minimum and average temperature ranged from 31.9-33.9oC, 22.2-26.3oC and 26.9-29.5oC, respectively on rice crop. No damage of PSB was observed from the second fortnight of April to first week of July. Small peaks of PSB incidence were observed on wheat crop during the months of December and February. The values of correlation coefficient (r) between PSB incidence and maximum, minimum, average temperature and sunshine hrs were -0.19, -0.005 -0.11 and -0.27 respectively and they were non-significant at (p=0.05%). The incidence of S. inferens has statistically significant and positive correlation (r = 0.53) with relative humidity. Average relative humidity of 80 per cent is favourable for its damage. Similarly, a positive and non-significant correlation (r=0.15) of PSB incidence was recorded with rainfall.Â